The Introduction of North Sumatera Culture to Grow The Spirit of Nationalism - Soeparno, Wahyu Sugeng Imam; Simatupang, Dewi Ratna Sari; Fauzie, Syarief; Hasibuan, Widya Sartika; Gurning, Herfita Rizki Hanasah (Ilin Institute, 2024)
Community service activities carried out at Sekolah Indonesia Kuala Lumpur aim to increase students' understanding of Indonesian customs and culture, especially North Sumatra. The implementation method shown to partners is to use media that illustrates and provides clear information and knowledge about the diversity of customs and culture in North Sumatra, through exposure, question and answer discussions and video screenings of various dances in North Sumatra, which are played directly by students of the Development Economics Study Program, University of North Sumatra, as well as video screenings of traditional houses in North Sumatra, tribes originating from North Sumatra, to traditional houses in North Sumatra. Partners are expected to contribute to increasing the knowledge and understanding of Indonesian School Kuala Lumpur students towards ethnic and cultural diversity in North Sumatra and support a sense of nationalism in order to preserve these customs and cultures.